DETECTION OF U2R ATTACKS BY MEANS OF A MULTILAYER NEURAL NETWORK - Пахомова, Вікторія; Мостинець, Владислав (SWorldJournal, 2024)
As a research method, multi layer neural network (MLNN) configurations 41-1-Х-4 were used, where 41 is the number of input neurons; 1 – the number of hidden layers; X – the number of hidden neurons; 4 – the number of resultant neurons created using the Ne